Component analysis of enhanced recovery pathways for esophagectomy. Issue 10 (19th July 2017) - Markar, S. R.; Naik, R.; Malietzis, G.; Halliday, L.; Athanasiou, T.; Moorthy, K.
Summary: The objective of this systematic review is to identify key components of enhanced recovery protocols (ERP) that lead to improved length of hospital stay (LOS) following esophagectomy. Relevant electronic databases were searched for studies comparing clinical outcome from esophagectomy followed by a conventional pathway versus ERP. Relevant outcome measures were compared and metaregression was performed to identify the key ERP components associated with reduced in LOS. Thirteen publications were included, ERP was associated with no changes in in-hospital mortality, total complications, anastomotic leak, or pulmonary complications compared with a conventional pathway, however LOS was reduced in the ERP group. Metaregression identified that immediate extubation was associated with reduced LOS (OR = −0.51, 95%CI −0.77 to −0.25; P  < 0.01). Several postoperative factors were associated with a significant reduction in length of hospital stay, and in order of most important were (i) gastrograffin swallow ≤5 days (OR = −4.27, 95%CI −4.50 to −4.03); (ii) mobilization on postoperative day ≤1 (OR = −2.49, 95%CI −2.63 to −2.34); (iii) removal of urinary catheter ≤2 days (OR = −0.99, 95%CI −1.15 to −0.84); (iv) oral intake with at least sips of fluid ≤1 day (OR = −0.96, 95%CI −1.24 to −0.68); (v) enteral diet with feeding jejunostomy or gastrostomy ≤ 1 day (OR = −0.57, 95%CI −0.80 to −0.35) and (vi) epidural removal ≤ 4 days (OR = −0.17, 95%CI −0.27 to −0.07). Several core ERP components and principles appear to be associated with LOS reduction. These elements should form a part of the core ERP for the specialty, while surgical teams incorporate other elements through an iterative process.